المفردات الاصطلاحية في كتاب توضيح الأحكام للمستوى الخامس والاستفادة منها في إثراء لغة الطالبات - TIARA FARAHANI; ARIF TAUFIQURRAHMAN (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2016)
God has chosen and honored the Arabic language among the languages ​​in the world to make it the language of Islam, spread and famous wherever the spread of Islam. So that the Arabic language is the language of the goal and an intermediary to request the same science, the second language after the mother language being taught and gradually taught in some Islamic countries from around the world. The study aimed to identify and learn the terms and vocabulary in the book explaining the provisions of the explanation of blogging, and the detection of meanings and use them to enrich the language of students. And development and development in the skill of speech and reading, especially in learning and teaching Arabic language students at the University of Raya. And those who benefit from it for useful purposes such as trade, selling, buying and travel for the Umrah, for example. In this study, the researcher followed the descriptive approach and took the method of content analysis. Research focused on Maktoob. This research is limited to the analysis of the conventional vocabulary related to the book explaining the provisions of the explanation of the attainment of Al-Maram. The study proved that there are 81 terms in the book explaining the provisions and can be used to enrich the language of students at the University of Al-Raya and all the learner and teacher of the Arabic language for non-religious speakers for religious and secular purposes.